Immune responses during COVID-19 breakthrough cases in vaccinated children and adolescents - Rivera-Pérez, Daniela; Méndez, Constanza; Diethelm-Varela, Benjamín; Melo-González, Felipe; Vázquez, Yaneisi; Meng, Xing; Xin, Qianqian; Fasce, Rodrigo A.; Fernández, Jorge; Mora, Judith; Ramirez, Eugenio; Acevedo, Mónica L.; et al. (Frontiers in Immunology, 2024)
Background Vaccine effectiveness against SARS-CoV-2 infection has been somewhat limited due to the widespread dissemination of the Omicron variant, its subvariants, and the immune response dynamics of the naturally infected with the virus. Methods Twelve subjects between 3-17 years old (yo), vaccinated with two doses of CoronaVac®, were followed and diagnosed as breakthrough cases starting 14 days after receiving the second dose. Total IgGs against different SARS-CoV-2 proteins and the neutralizing capacity of these antibodies after infection were measured in plasma. The activation of CD4+ and CD8+ T cells was evaluated in peripheral blood mononuclear cells stimulated with peptides derived from the proteins from the wild-type (WT) virus and Omicron subvariants by flow cytometry, as well as different cytokines secretion by a Multiplex assay. Results 2 to 8 weeks post-infection, compared to 4 weeks after 2nd dose of vaccine, there was a 146.5-fold increase in neutralizing antibody titers against Omicron and a 38.7-fold increase against WT SARS-CoV-2. Subjects showed an increase in total IgG levels against the S1, N, M, and NSP8 proteins of the WT virus. Activated CD4+ T cells showed a significant increase in response to the BA.2 subvariant (p<0.001). Finally, the secretion of IL-2 and IFN-γ cytokines showed a discreet decrease trend after infection in some subjects. Conclusion SARS-CoV-2 infection in the pediatric population vaccinated with an inactivated SARS-CoV-2 vaccine produced an increase in neutralizing antibodies against Omicron and increased specific IgG antibodies for different SARS-CoV-2 proteins. CD4+ T cell activation was also increased, suggesting a conserved cellular response against the Omicron subvariants, whereas Th1-type cytokine secretion tended to decrease. Clinical Trial Registration clinicaltrials.gov #NCT04992260